2017
DOI: 10.1176/appi.ps.201600182
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Coverage and Treatment Use Under the Affordable Care Act Among Adults With Mental and Substance Use Disorders

Abstract: Sizable increases in coverage for adults with mental disorders and adults with substance use disorders were identified in the year following the 2014 ACA expansions; however, low treatment rates among this population remain a concern. Initiatives to engage the newly insured in treatment are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 19 publications
2
39
1
2
Order By: Relevance
“…Our findings contribute to the emerging literature on the impact of the ACA (Gonzales et al 2016; Saloner et al 2017), whose findings suggest that access to health insurance and utilization of services has increased (Wherry and Miller 2016), health care related financial burdens have decreased (Ali et al 2016b), and barriers to paying for health services have been reduced (Chen et al 2016). Our findings are consistent with this, in that we found that adults with SPD were more likely to have health insurance coverage and experience lower barriers in accessing treatments after 2014.…”
Section: Discussionsupporting
confidence: 58%
“…Our findings contribute to the emerging literature on the impact of the ACA (Gonzales et al 2016; Saloner et al 2017), whose findings suggest that access to health insurance and utilization of services has increased (Wherry and Miller 2016), health care related financial burdens have decreased (Ali et al 2016b), and barriers to paying for health services have been reduced (Chen et al 2016). Our findings are consistent with this, in that we found that adults with SPD were more likely to have health insurance coverage and experience lower barriers in accessing treatments after 2014.…”
Section: Discussionsupporting
confidence: 58%
“…These changes may have helped reduce financial barriers to treatment for persons with opioid use disorders. One study found that the prevalence of uninsured decreased among persons with any substance use or mental health disorder in 2014 following the PPACA insurance expansion (Saloner et al, 2017). The present study examines insurance coverage and treatment access among persons with opioid use disorders, who may differ from the larger population of persons with substance use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Underfunding is a legacy of the historical marginalization of drug treatment, where limited funding for treatment has come primarily from state and local funding grants rather than insurance programs (Buck, ). The 2008 Mental Health Parity and Addiction Equity Act in tandem with Affordable Care Act of 2010 have had the positive effects of increasing the number of individuals in addiction treatment financed through health insurance through private insurance or the Medicaid program (Saloner et al., ). These recent policy changes have also facilitated broader access to evidence‐based treatment for OUD through regulatory changes in benefit design (Horgan et al., ).…”
Section: Approaches To Broaden Use Of Pharmacological Treatments For Oudmentioning
confidence: 99%